Assessment of clonal fidelity of doubled haploid line of marigold (Tagetes erecta) using microsatellite markers - UZMA MEHRAJ; SAPNA PANWAR; KANWAR PAL SINGH; NAMITA NAMITA; RENU PANDEY; AMOLKUMAR U SOLANKE; NIHARIKA MALLICK; SURENDRA KUMAR (The Indian Journal of Agricultural Sciences, 2019)
In vitro multiplied plants of doubled haploid line of marigold (Tagetes erecta L.) derived through ovule culture, were subjected to evaluation of genetic uniformity using SSR markers in order to evaluate their genetic stability and/ or detect likely existing variations among in vitro derived plantlets. Leaf samples were taken from randomly selected 13 plants at post acclimatization stage, for checking the clonal fidelity of the in vitro derived regenerants by comparing them with the mother plant from which the leaf explants were taken. Out of 36 primers, 12 showed amplification in which clear and reproducible PCR profiles. Analysis of individual primers revealed that SSR primers produced same banding pattern which were shared by the in vitro leaf derived regenerants and the donor mother plant, which indicated that there was no variation observed within the tissue culture raised plants. All the banding profiles produced were monomorphic and were similar to those of the mother plant, and hence, showed that plants were true to type. Information presented in the study indicated that the in vitro regenerated plants were identical to the mother plant.